ACCELEROMETRIC DATA AND WEB PORTAL FOR THE VERTICAL CORINTH GULF SOFT SOIL ARRAY (CORSSA) - Kassaras, I.; Roumelioti, Z.; O.-J. Ktenidou; K. Pitilakis; Voulgaris, N.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2016)
Strong motion data recorded during the 15-year operation of the CORinth Gulf Soft Soil Array (CORSSA) in the highly seismic region of Aegion have been homogenized and organized in a MySQL database. In the present work we describe the contents of the database and the web portal through which these data are publicly accessible. CORSSA comprises one surface and four downhole 3-D broadband accelerometric stations. It was installed in 2002, in the framework of European project CORSEIS, aiming at gathering data for studying site effects, liquefaction, and non-linear behaviour of soils, as well as earthquake source properties. To date, the array has recorded 549 local and regional events with magnitudes ranging from 1.1 to 6.5. Although the vast majority of the recorded events caused weak ground motion at the CORSSA site, the scientific value of the data set pertains to the sparsity of this kind of infrastructure in most parts of the world.
Keywords: earthquake; site effects; strong motion database